Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) Profiling for Quinolinone Alkaloids and Phenolic Metabolites in a Bioactive Fraction of Indonesian Yacon (Smallanthus sonchifolius) Tuber Extract - Eka Hendryanny; Widayanti; Lelly Yuniarti (Global Medical & Health Communication (GMHC), 2025)
Yacon (Smallanthus sonchifolius) is a functional tuber rich in fructooligosaccharides, phenolic compounds, and diverse secondary metabolites with potential health-promoting properties. Despite its increasing use, the comprehensive characterization of its bioactive constituents, particularly those derived from plants cultivated in Indonesia, remains limited. This study aims to identify and characterize the major bioactive components of ethanolic yacon tuber extract using liquid chromatography-tandem mass spectrometry (LC-MS/MS). This descriptive, exploratory investigation of natural product phytochemistry was conducted from June to July 2025—fresh tubers were collected from Lembang, West Bandung. The samples were subjected to ethanol maceration, and LC-MS/MS analysis was performed on a bioactive fraction (Rf 0.52) obtained from preliminary thin-layer chromatography (TLC) fractionation of the crude ethanolic extract, using positive electrospray ionization and gradient elution. Compound annotation was performed using UNIFI software. LC–MS/MS profiling revealed 15 predominant secondary metabolites, with retention times ranging from 5.41 to 13.18 minutes and mass-to-charge (m/z) ratios of 255.35–459.48. Early-retention peaks comprised polar constituents, such as sucrose and nicotianamine, a metal-chelating amino acid known to enhance iron bioavailability. Mid-retention peaks included phenolic acids and flavonoids, notably chlorogenic acid and jaceosidin. High-retention peaks were dominated by hydrophobic alkaloids, with 4,7,8-trimethyl-3-(3-methylbut-2-enyl)-1H-quinolin-2-one identified as the most abundant compound (56.42%), followed by senecionine (9.36%) and nonadecan-2-amine (6.75%). In conclusion, West Bandung yacon tubers contain a diverse spectrum of alkaloids, flavonoids, and phenolic derivatives that may contribute to their pharmacological potential. The results provide an essential phytochemical foundation for future studies evaluating bioactivity and toxicological assessment using targeted in vitro and in vivo approaches.